Identifying adhesive components in a model tunicate. (28th October 2019) - Zeng, Fan; Wunderer, Julia; Salvenmoser, Willi; Ederth, Thomas; Rothbächer, Ute
Abstract : Tunicates populate a great variety of marine underwater substrates worldwide and represent a significant concern in marine shipping and aquaculture. Adhesives are secreted from the anterior papillae of their swimming larvae, which attach and metamorphose into permanently adhering, filter-feeding adults. We recently described the cellular composition of the sensory adhesive organ of the model tunicate Ciona intestinalis in great detail. Notably, the adhesive secretions of collocytes accumulate at the tip of the organ and contain glycoproteins. Here, we further explore the components of adhesive secretions and have screened for additional specificities that may influence adhesion or cohesion of the Ciona glue, including other carbohydrate moieties, catechols and substrate properties. We found a distinct set of sugar residues in the glue recognized by specific lectins with little overlap to other known marine adhesives. Surprisingly, we also detect catechol residues that likely originate from an adjacent cellular reservoir, the test cells. Furthermore, we provide information on substrate preferences where hydrophobicity outperforms charge in the attachment. Finally, we can influence the settlement process by the addition of hydrophilic heparin. The further analysis of tunicate adhesive strategies should provide a valuable knowledge source in designing physiological adhesives or green antifoulants. This article is part of the theme issue 'Transdisciplinary approaches to the study of adhesion and adhesives in biological systems'.